(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: A period of starvation is common practice after intestinal anastomosis. Starved patient became malnourished and underwent catabolic state, impairing the host immune response and thus increasing the risk of postoperative infections thereby long hospital stay. Objective: To observe the outcome of early oral feeding in patients having primary repair of traumatic intestinal injury and to assess its beneficial effect. Methods: This prospective observational study was conducted on 80 patients who underwent urgent intestinal resection with or without covering stoma in the Department of Casualty Surgery at Dhaka Medical College Hospital. Results: Early oral feeding is safe in the recently performed anastomosis even in emergency situations as there were no cases of clinical anastomotic dehiscence and no increase in morbidity. Among 80 patients 58(72.5%) patients had no complaints; rest 22(27.5%) patients had complication. Wound infection seen in 14(17.5%) patients among them 8(10%) patients had burst abdomen and 1(1.25%) patient had intraabdominal abscess. 14(17.5%) patients had chest infection. 10(12.5%) patients complained nausea and among them 8(10%) patients suffered from few episodes of vomiting. 1(1.25%) patient had diarrhoea. Abdominal distension was seen in 9(11.25%) patients. Hospital stay was significantly shorter in with a mean length of stay (9 ± 1) days. No hospital readmission rate was recorded. Conclusion: Early postoperative feeding is timely, safe and tolerable after emergency intestinal resection anastomosis without raised morbidity and mortality and has a considerable reduction in hospital stay with its physical, psychological and fiscal benefits. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 75-79